Radial and Ulnar Artery Size in Bangladeshi Population Coming for Cardiac Catheterization (Ibrahim Cardiac Medical Journal, 2015)
Background: Transradial approach has now become a preferred route for cardiac catheterization. However, smaller size of the artery, being liable to sustain injury during the procedure, this approach may even lead to permanent occlusion. This study is intended to measure the diameter of radial and ulnar artery and to identify the factors influencing the size of the arteries.Methods: Using two dimensional ultrasound and Doppler examination, the inner diameter of right radial and ulnar arteries were measured in 373 consecutive patients with normal Allen test who underwent coronary angiogram (CAG) and/or percutaneous coronary intervention (PCI) through trans-radial approach in Ibrahim Cardiac Hospital and Research Institute (ICHRI), Dhaka from August 2013 to September 2014.Results: The mean sizes of the radial and ulnar arteries were 2.2 ± 0.3 mm and 2.1 ± 0.3 mm respectively. There was no significant correlations of age with size of radial and ulnar artery (r = 0.055, p = 0.290 and r = 0.010, p = 0.846 respectively). However, sex was found to be associated with size of the arteries with male having greater size compared to their female counterparts (2.1±0.3 vs. 2.0±0.2 mm, p = 0.001 and 2.0 ± 0.3 vs. 1.9 ± 0.3 mm, p = 0.006 respectively). BMI was found to bear significant correlation with size of radial and ulnar artery (r = 0.137, p = 0.008 and r = 0.121, p = 0.019 respectively). Likewise, smokers and dyslipidaemics had bigger size of radial and ulnar arteries compared to their non-smoker and non-dyslipidemic counterparts (p = 0.015 & p = 0.017 respectively and p < 0.001 & p =0.011 respectively). However, hypertension and diabetes did not influence the size of radial and ulnar arteries (p = 0.559 and p = 0.916; p = 0.778 and p = 0.931 respectively).Conclusion: Diameter of radial and ulnar arteries of Bangladeshi population is a bit smaller but does not vary much with other population around the world. Male, smoker, obese and dyslipidaemic persons generally have bigger size of the radial and ulnar arteries, while age, hypertension and diabetes do not bear any relationship with size of the arteries.Ibrahim Cardiac Med J 2013; 3(1&2): 21-26